Pengaruh Internal Audit dan Whistleblowing System terhadap Pencegahan Fraud pada BRI Regional Audit Office Bandung - Irsan Herlandi Putra; Juliyanto Juliyanto; Andy Yusuf Martua; Akhmad Farikhin; Sani Susanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research was conducted at BRI Regional Audit Office Bandung. The purpose of this study is to determine how much influence internal audit and whistleblowing system partially and simultaneously have on fraud prevention. The theories used in this study are agency theory and pentagon fraud theory. The population in this study is all BRI Regional Audit Office Bandung workers. This study used nonprobability sampling techniques using purposive sampling techniques. The sample of this study was all auditors of BRI Regional Audit Office Bandung, which was 41 respondents and data collection using questionnaires. This research uses a quantitative approach with descriptive and verifiative methods. The statistical tests used are validity tests and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. The results of the analysis were processed using the IBM SPSS Statistics 26 program. The correlation results show that internal audit, whistleblowing system and fraud have a very strong relationship with positive direction. Meanwhile, the results of multiple linear regression analysis show that internal audit and whistleblowing system have a significant effect on fraud prevention both partially and simultaneously.